VD_FINDINFO HC / 2016 / 319 vom 21. März 2016 - VD Tribunal cantonal (2016)
FRAIS JUDICIAIRES, DÉCISION SUR FRAIS, RÉPARTITION DES FRAIS | 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 107 al. 1 let. c CPC (CH), 107 al. 1 let. f CPC (CH)